If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 = (3x + 13)(5x + -7) Reorder the terms: 90 = (13 + 3x)(5x + -7) Reorder the terms: 90 = (13 + 3x)(-7 + 5x) Multiply (13 + 3x) * (-7 + 5x) 90 = (13(-7 + 5x) + 3x * (-7 + 5x)) 90 = ((-7 * 13 + 5x * 13) + 3x * (-7 + 5x)) 90 = ((-91 + 65x) + 3x * (-7 + 5x)) 90 = (-91 + 65x + (-7 * 3x + 5x * 3x)) 90 = (-91 + 65x + (-21x + 15x2)) Combine like terms: 65x + -21x = 44x 90 = (-91 + 44x + 15x2) Solving 90 = -91 + 44x + 15x2 Solving for variable 'x'. Combine like terms: 90 + 91 = 181 181 + -44x + -15x2 = -91 + 44x + 15x2 + 91 + -44x + -15x2 Reorder the terms: 181 + -44x + -15x2 = -91 + 91 + 44x + -44x + 15x2 + -15x2 Combine like terms: -91 + 91 = 0 181 + -44x + -15x2 = 0 + 44x + -44x + 15x2 + -15x2 181 + -44x + -15x2 = 44x + -44x + 15x2 + -15x2 Combine like terms: 44x + -44x = 0 181 + -44x + -15x2 = 0 + 15x2 + -15x2 181 + -44x + -15x2 = 15x2 + -15x2 Combine like terms: 15x2 + -15x2 = 0 181 + -44x + -15x2 = 0 Begin completing the square. Divide all terms by -15 the coefficient of the squared term: Divide each side by '-15'. -12.06666667 + 2.933333333x + x2 = 0 Move the constant term to the right: Add '12.06666667' to each side of the equation. -12.06666667 + 2.933333333x + 12.06666667 + x2 = 0 + 12.06666667 Reorder the terms: -12.06666667 + 12.06666667 + 2.933333333x + x2 = 0 + 12.06666667 Combine like terms: -12.06666667 + 12.06666667 = 0.00000000 0.00000000 + 2.933333333x + x2 = 0 + 12.06666667 2.933333333x + x2 = 0 + 12.06666667 Combine like terms: 0 + 12.06666667 = 12.06666667 2.933333333x + x2 = 12.06666667 The x term is 2.933333333x. Take half its coefficient (1.466666667). Square it (2.151111112) and add it to both sides. Add '2.151111112' to each side of the equation. 2.933333333x + 2.151111112 + x2 = 12.06666667 + 2.151111112 Reorder the terms: 2.151111112 + 2.933333333x + x2 = 12.06666667 + 2.151111112 Combine like terms: 12.06666667 + 2.151111112 = 14.217777782 2.151111112 + 2.933333333x + x2 = 14.217777782 Factor a perfect square on the left side: (x + 1.466666667)(x + 1.466666667) = 14.217777782 Calculate the square root of the right side: 3.770646865 Break this problem into two subproblems by setting (x + 1.466666667) equal to 3.770646865 and -3.770646865.Subproblem 1
x + 1.466666667 = 3.770646865 Simplifying x + 1.466666667 = 3.770646865 Reorder the terms: 1.466666667 + x = 3.770646865 Solving 1.466666667 + x = 3.770646865 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.466666667' to each side of the equation. 1.466666667 + -1.466666667 + x = 3.770646865 + -1.466666667 Combine like terms: 1.466666667 + -1.466666667 = 0.000000000 0.000000000 + x = 3.770646865 + -1.466666667 x = 3.770646865 + -1.466666667 Combine like terms: 3.770646865 + -1.466666667 = 2.303980198 x = 2.303980198 Simplifying x = 2.303980198Subproblem 2
x + 1.466666667 = -3.770646865 Simplifying x + 1.466666667 = -3.770646865 Reorder the terms: 1.466666667 + x = -3.770646865 Solving 1.466666667 + x = -3.770646865 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.466666667' to each side of the equation. 1.466666667 + -1.466666667 + x = -3.770646865 + -1.466666667 Combine like terms: 1.466666667 + -1.466666667 = 0.000000000 0.000000000 + x = -3.770646865 + -1.466666667 x = -3.770646865 + -1.466666667 Combine like terms: -3.770646865 + -1.466666667 = -5.237313532 x = -5.237313532 Simplifying x = -5.237313532Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.303980198, -5.237313532}
| 20%*5000= | | (3x^2+7x-4)+(2x^2-3x-9)= | | 5-9n=31 | | 3h+2h+9=54 | | 13=5x+1-3x | | .20*5000= | | 2975+X(175.75)=5962.72 | | 9+-5x=12+-1(6x+7) | | 0.3(4x-2)=-0.8x+9.4 | | 2c^2+9c+10=0 | | 6000-1240= | | (X+41)+95=x+78 | | 2x+9-x=9+2x-6 | | 74=8(c+4)-4 | | 4760/45= | | 2.5=3.7-0.4x | | 3log(x)=11 | | 5+4x=6x+5-2x | | 8x-1+9x=7x+3-9x | | 2v-13=11 | | f(x)=2x^2+9x-5 | | x=y-0.8 | | 2.6x-1.8y=5.5x-0.8y | | 5x/8-8=x/14+13 | | 5x+9=6(x+2) | | 4y-5=20y+11 | | 3n+yr=r-8h | | -6(3m-5)=-78 | | 2y+4=-6y+10+4y | | x^2+y^2-16*(-2)+8*(-3)-10=0 | | 9(s+8)-23=76 | | 2y+4=8y |